Sensitivity of energy system investments to policy regulation changes: Application of the blue sky catastrophe - Anton Bondarev; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2017)
In this paper we argue, that the interaction of technology and economic policy regulations in the energy sector may be described by the so-called slow-fast class of dynamical systems. It is known that such systems may exhibit the blue sky catastrophe, a special type of bifurcation. Application of this result allows us to argue that caution is needed when updating economic policies in the energy sector to avoid the onset of catastrophic developments in the system's transformation, when energy system dynamics becomes unresponsive to policy updates.
Keywords: L51; Q48; C6; C02; 330; energy infrastructure; investments cycle; economic policy; slow-fast systems; blue sky catastrophe